Implementation of SHA-256 and Reed-Solomon Algorithms in Quick Response (QR) Codes at the Class IIB Correctional Facility System in Pati Regency - Rehan Angger Pradata; Bambang Agus Herlambang; Khoiriya Latifah (SISTEMASI, 2026)
Correctional facilities play an important role in the rehabilitation and supervision of inmates. In practice, the process of recording the number of inmates in each room is still largely performed manually, requiring considerable time and increasing the risk of recording errors. This approach also reduces the efficiency of correctional officers in conducting routine checks. Therefore, a system capable of providing fast, accurate, and secure information is needed. This study aims to implement a QR Code-based information system at the Class IIB Correctional Facility in Pati Regency to support inmate-room data management. A QR Code is placed at the entrance of each room and contains information regarding the room number, room capacity, and number of inmates occupying the room. To protect data integrity, the SHA-256 algorithm is employed to generate hash values for verifying data integrity and preventing unauthorized modification of information. In addition, the Reed–Solomon algorithm is implemented as an error-correction mechanism to ensure that QR Codes remain scannable even when partially damaged. The system was developed as a web-based application and can be accessed by correctional officers using mobile devices to scan the QR Codes. The results demonstrate that integrating QR Codes with SHA-256 and Reed–Solomon algorithms improves the efficiency of inmate-room data verification, accelerates information access, enhances data integrity and security, and reduces errors associated with manual data recording.